Voltammetric Detection of Zn2+ Ions Using a Glassy Carbon Electrode Modified with Napa-Soil-Derived NiAl₂O₄ - Dhea Septiani; Mawardi Mawardi; Indang Dewata; Umar Kalmar Nizar; Okta Suryani (Universitas Pendidikan Mandalika, 2026)
This study reports the development of a glassy carbon electrode (GCE) modified with NiAl2O4 derived from napa soil for the voltammetric detection of Zn2+ ions. The modified electrode was prepared using a drop-casting method and characterized in 4.0 mM K3[Fe(CN)6] with 0.1 M KCl as the supporting electrolyte. The results showed an increase in oxidation peak current from 19.93 µA (bare GCE) to 26.80 µA and reduction peak current from −19.03 µA to −24.29 µA after modification, indicating enhanced electron transfer. Zn2+ detection was carried out in the concentration range of 1–3 mM, where the reduction peak current increased from −85.49 µA to −170.83 µA with increasing concentration. A linear relationship between concentration and current response was obtained with a regression equation of y = -42.67x – 40.42 and a correlation coefficient (R2 = 0.9907), indicating good linearity of the sensor. The limit of detection (LOD) was calculated to be 0.21 mM. Among the tested supporting electrolytes, 0.1 M KCl provided the highest and most stable current response. Although the modified electrode shows improved performance, the detection range is still limited to the millimolar level, and further studies are required to evaluate selectivity, reproducibility, and applicability in real samples. These findings demonstrate the potential of napa-soil-derived NiAl2O4 as a sustainable and cost-effective material for electrochemical sensing applications.